Compound heterozygous variants in OTULIN are associated with fulminant atypical late‐onset ORAS. Issue 3 (16th February 2022) - Zinngrebe, Julia; Moepps, Barbara; Monecke, Thomas; Gierschik, Peter; Schlichtig, Ferdinand; Barth, Thomas F E; Strauß, Gudrun; Boldrin, Elena; Posovszky, Carsten; Schulz, Ansgar; Beringer, Ortraud; Rieser, Eva; et al.
Abstract: Autoinflammatory diseases are a heterogenous group of disorders defined by fever and systemic inflammation suggesting involvement of genes regulating innate immune responses. Patients with homozygous loss‐of‐function variants in the OTU‐deubiquitinase OTULIN suffer from neonatal‐onset OTULIN‐related autoinflammatory syndrome (ORAS) characterized by fever, panniculitis, diarrhea, and arthritis. Here, we describe an atypical form of ORAS with distinct clinical manifestation of the disease caused by two new compound heterozygous variants (c.258G>A (p.M86I)/c.500G>C (p.W167S)) in the OTULIN gene in a 7‐year‐old affected by a life‐threatening autoinflammatory episode with sterile abscess formation. On the molecular level, we find binding of OTULIN to linear ubiquitin to be compromised by both variants; however, protein stability and catalytic activity is most affected by OTULIN variant p.W167S. These molecular changes together lead to increased levels of linear ubiquitin linkages in patient‐derived cells triggering the disease. Our data indicate that the spectrum of ORAS patients is more diverse than previously thought and, thus, supposedly asymptomatic individuals might also be affected. Based on our results, we propose to subdivide the ORAS into classical and atypical entities. Synopsis: The OTULIN‐Related Autoinflammatory Syndrome (ORAS) is known to be caused by homozygous variants in the OTULIN gene. This study discovers that two new compound‐heterozygous variants in OTULIN are associated with an atypical, but potentially fatal, late‐onset form of ORAS. Atypical ORAS is characterized by multiorgan abscess formation and bears the risk of being clinically inapparent. OTULIN variants p.M86I and p.W167S disrupt OTULIN function leading to increased levels of linear ubiquitin linkages in patient‐derived fibroblasts and B cells. Molecularly, atypical ORAS resembles classical ORAS with enhanced TNF production in monocytes, but diminished TNF‐induced gene activation and sensitization to TNF‐mediated cell death (in the presence of cycloheximide) in fibroblasts. Anti‐TNF therapy with Adalimumab resulted in normalization of the patient's inflammatory plasma protein profile suggesting that patients with atypical ORAS might benefit from TNF‐blocking agents as seen in patients with classical ORAS. Abstract : The OTULIN‐Related Autoinflammatory Syndrome (ORAS) is known to be caused by homozygous variants in the OTULIN gene. This study discovers that two new compound‐heterozygous variants in OTULIN are associated with an atypical, but potentially fatal, late‐onset form of ORAS.